Management of compound odontoma with 70 denticles and impacted lateral incisor over an 8-year follow-up - J Jeevarathan; N C Jananivinodhini; A Ponnudurai; M VijayaKumar; Kanthaswamy A Chidambaranathan (Wolters Kluwer Medknow Publications, 2022)
Odontomas are benign developmental tumors formed by the improper growth of completely differentiated epithelial and mesenchymal cells of odontogenic origin. The etiology of odontoma is unknown and it is detected during routine radiographic examination. The ideal management is early detection and surgical enucleation. The commonly associated clinical problems of odontomas are delayed exfoliation of primary teeth, delayed eruption or impaction of permanent teeth, displacement of teeth, root resorption, congenital missing, and widening of follicular space. Here, we describe a unique case of compound odontoma with a high number of denticles managed based on a definite decision support system over 8 years. An 8-year-old boy with 70 denticles in the left maxillary region underwent enucleation. On periodic follow-up, the associated impacted lateral incisor was extruded orthodontically.